133 Langendorff-free method for isolation of cardiomyocytes from the adult and neonatal mouse hearts. (June 2018) - Pavlovic, Davor; Ackers-Johnson, Matthew; Luu, Tuan; Li, Yiqing; Holmes, Andrew P; O'Brien, Sian-Marie; Hepburn, Claire; Fabritz, Larissa; Kirchhof, Paulus; Foo, Roger
Abstract : Rationale: Isolation of high quality myocytes from the adult mouse heart has traditionally required Langendorff perfusion systems, involving a high degree of technical skill. We recently introduced a simplified Langendorff-free protocol, utilising direct ventricular injection of digestion buffers ex-vivo . 1 Here we address questions raised regarding direct comparison against the established Langendorff method, and the amenability to isolating myocytes from infarcted and neonatal hearts. Objective: The objective was to conduct direct comparisons of functional and signalling characteristics of myocytes isolated using Langendorff and injection methodologies, and to test the injection protocol for isolation of myocytes from infarcted hearts, healthy adult atria, and neonatal mouse ventricles. Methods and results: Cardiac myocytes were isolated from healthy adult mice using Langendorff and injection protocols. We asesed some of the key cellular calcium handling parameters (see figure 1), contractility and sodium channel biophysical characteristics, with no significant differences between the methodologies identified. Diastolic sarcomere length measurements in quiescent cells (1.71 ± 0.04 Langendorff v 1.82 ± 0.03 Injection; n=19 cells from 4 hearts; *p<0.05) indicate that injection method improves relaxation compared to Langendorff, however, no significant differences were observed in other stress indicators assesed including diastolic calcium, PKC-alpha activation, ERK1/2 phosphorylation and phospholemman phosphorylation. Myocytes were subsequently isolated from mouse hearts after surgically-induced infarction using the injection method, and also from healthy adult mouse atria, and neonatal mouse ventricles, using modifications of this method. Yields of ventricular myocytes isolated from infarcted hearts were predictably reduced to 64.2±6.4% rod-shaped cells. Viable atrial myocytes were obtained from healthy adult hearts, and exceptionally high yields (92.7±2.3%) of viable ventricular myocytes were obtained from neonatal mouse hearts. Conclusions: We present a novel, robustly characterised method, demonstrating isolation of viable cardiac myocytes from adult mouse heart. Cardiomyocytes isolated using the injection methodology are of equal quality to those isolated using traditional Langendorff methods. The injection method can be used to obtain good yields of healthy myocytes from infarcted hearts. Furthermore, modifications to the injection method permit the isolation of myocytes from the adult mouse atria, and neonatal mouse ventricles. Reference: . Ackers-Johnson, et al. Circ Res. 2016;119(8):909–20.